PERBEDAAN KARAKTERISTIK FISIK DAN KIMIA MANGO INFUSED TEA BERDASARKAN JENIS MANGGA DAN LAMA PERENDAMAN - Siallagan, Edwin; Widyasaputra, Reza; Widyowanti, Reni Asuti (Fakultas Pertanian Universitas Alkhairaat Palu, 2023)
Tea beverage as water substitute in infused water drinks had not been widely used. One of fruit could be used was mango. Mango infused tea was tea with soaked mango for certain time. The purpose of this study was to analyze the physical and chemical characteristics of mango infused tea. The research method used is a 2-factor complete block design. The first factor was the cultivar of mango (kweni, golek, and arumanis) and the second factor was the different soaking times (4, 6, and 8 hours) and then analyzed. The research method used is a 2-factor complete block design. The first factor was the cultivar of mango (kweni, golek, and arumanis) and the second factor was the different soaking times (4, 6, and 8 hours) and then analyzed for antioxidants and vitamin C. Data analysis was carried out using two-way ANOVA, the significant factor was analyzed by Duncan's test. The results showed that generaly the longer of soaking time the greater of color changes. Kweni mango with 4 hours of soaking time obtained the highest levels of antioxidants and the type of arumanis mango with 8 hours of soaking time obtained the highest levels of highest vitamin C. Arumanis mango with 8 hours of soaking showed the highest pH value.